2019
DOI: 10.1111/pce.13678
|View full text |Cite
|
Sign up to set email alerts
|

Light‐ and temperature‐entrainable circadian clock in soybean development

Abstract: In plants, the spatiotemporal expression of circadian oscillators provides adaptive advantages in diverse species. However, the molecular basis of circadian clock in soybean is not known. In this study, we used soybean hairy roots expression system to monitor endogenous circadian rhythms and the sensitivity of circadian clock to environmental stimuli. We discovered in experiments with constant light and temperature conditions that the promoters of clock genes GmLCLb2 and GmPRR9b1 drive a self‐sustained, robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 102 publications
1
46
0
Order By: Relevance
“…For each sample, color corresponds to the z-score given by the sample's TPM. ZT, hours after dawn.TPM, transcripts per million et al, 2013;Liew et al, 2017;Locke et al, 2018;Marcolino-Gomes et al, 2014;Wang et al, 2020) (Figure 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For each sample, color corresponds to the z-score given by the sample's TPM. ZT, hours after dawn.TPM, transcripts per million et al, 2013;Liew et al, 2017;Locke et al, 2018;Marcolino-Gomes et al, 2014;Wang et al, 2020) (Figure 2).…”
mentioning
confidence: 99%
“…). The circadian clock-related transcription factors in soybeans include Late elongated hypocotyl/circadian clock associated (LCL), TOC1, PRR, GIGANTEA (GI), LUX ARRHYTHMO (LUX), and Early flowering 4 (ELF4)(Cheng et al, 2019;Li et al, 2013;Liew et al, 2017;Wang et al, 2020). The expression of these key circadian clock-related genes showed diurnal changes both in the leaves and roots and displayed a similar expression tendency as observed in previous studies(Cheng et al, 2019; Li F I G U R E 3 Phase sorted heatmap showing diurnally oscillating gene expressions in leaves (a) and roots (b).…”
mentioning
confidence: 99%
“…In general, the circadian rhythm pathway is associated with the photoperiod pathway, and endogenous circadian rhythms are sensitive to light/dark stimuli 15,16 . The expression patterns of most genes involved in these two pathways showed sequential expression in this study (Fig.…”
Section: The Photoperiod Pathway Is the Dominant Pathway In Chinese Jmentioning
confidence: 99%
“…As a facultative short‐day plant, soybeans exhibit unique photoperiod sensitivity and geographical adaptation (Lu et al, 2017; Lu et al, 2020; Wang, Sun, et al, 2020). Recent studies have shown that a large proportion of the soybean transcriptome is directly regulated by the circadian clock (Li et al, 2019; Li et al, 2020; Wang, Sun, et al, 2020). Our previous research found that the expression of LHY‐CCA1‐LIKE orthologs, GmLCLa1 , GmLCLa2 , GmLCLb1 and GmLCLb2 , showed a nearly 24‐hr rhythm under free‐running conditions, with a peak around dawn, and mutation of GmLCLs caused a shortened circadian period and late flowering phenotype (Wang, Yuan, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%